Interactive persuasive learning elements among elderly: A measurement model - Zulkifli, Abdul Nasir; Ahmad, Mazida; Abu Bakar, Juliana Aida; Che Mat, Ruzinoor; Noor, N.M. (Penerbit UTM Press, 2015)
The increasing usage of computer technology in myriad fields involves almost all level of the society to interact with the technology. Although the receptions are going well, however, for certain level of ages in the society, the need seems to be difficult to them.Of the level, elderly is a must to be considered for designing and developing computer technology systems that suit them better.Hence, our study proposes a conceptual model of an interactive persuasive learning system to encourage the elderly to use a computer application for learning.This paper is part of our study that evaluates a measurement model of interactive elements of persuasive learning among elderly.This study used empirical study as a method for data collection. Data was collected from 300 elderly respondents and each respondent was supplied with a laptop to enable him/her to use the interactive course ware.The data was analyzed using the Structural Equation Modeling (SEM) with Analysis of Moment Structures (AMOS).The results have shown that the measurement model fits the data.Therefore, the model is suitable for interactive media among elderly. Further, this study intends to identify the relationship between the interactive media features and persuasive learning elements among elderly.